Use of strategic accounting tools to measure the effectiveness of the cost of quality, proposed accounting framework - Khaled, Walid Al Tayeb Omar (Arab Journal for Sciences and Research Publishing, 2017)
This study aimed to measure the effectiveness of the cost of quality in service organizations, through a list of measurement proposed depend on recent trends of accounting Strategic, through the integration methodology of the Total Quality Management and Accounting Measurement to balanced Scorecard for the measurement of the effectiveness of the cost of quality services, from the quantitative perspective proposal. Researcher try of this study give the accounting side on the measurement of balanced scorecard, in order to know whether the proposed integration of perspectives contributes to the cost-effective measure and is working on rationalization. The researcher used the descriptive analytical and inductive, and concluded that the proposed model provides the ability to measure accurately the cost of quality, and helps to improve the effectiveness of programs and after the experimental application of the model in a health service institutions , The study recommended that the success of the proposed model is based on the continued application him, and identifying standards for the form and the objective of each measure, and then find out the investigator in every year, and figure out the best global results for this measure until we get the optimal results.